Intimate partner violence among young women in Ibadan, Nigeria: are there slum and non-slum differences? - Omowumi O. Okedare; Olufunmilayo I. Fawole (BMC, 2023)
Abstract This study determined the past-year prevalence of physical, sexual and psychological intimate partner violence (IPV) and associated factors among young women in urban slums and non-slums of Ibadan, Nigeria. A cross-sectional study, using a multistage cluster sampling method was used to select 1050 ever-partnered young women aged between 18 and 24 years from the five Local Government Areas (LGAs) in Ibadan municipal. All localities were classified into slums and non-slums using the UN-Habitat 2003 criterion. Independent variables were respondents' and partners' characteristics. Dependent variables were physical, sexual and psychological IPV. Data were analysed using descriptive statistics and binary logistic regression model (α0.05). Prevalence of physical (31.4%, 13.4%), sexual (37.1%, 18.3%), and psychological IPV (58.6%, 31.5%) were significantly higher in the slum than non-slum communities. Multivariate analysis showed that secondary education (aOR:0.45, 95%CI: 0.21 - 0.92) reduced IPV experience while being unmarried (aOR:2.83, 95%CI: 1.28 - 6.26), partner's alcohol use (aOR:1.97, 95%CI: 1.22 - 3.18), and partner's relationship with other women (aOR:1.79, 95%CI: 1.10 -2.91) increased IPV experience in slum communities. In non-slum communities, having children (aOR:2.99, 95%CI: 1.05-8.51), non-consensual sexual debut (aOR: 1.88, 95%CI: 1.07-3.31) and witness of abuse in childhood (aOR:1.82: 95%CI: 1.01 - 3.28) increased experience of IPV. Acceptance of IPV and partner's witness of abuse in childhood increased experience of IPV in both settings. This study confirms that IPV is common among young women in Ibadan, Nigeria, but higher among women in slum communities. Findings also showed different factors associated with IPV in slum and non-slum communities. Therefore, targeted interventions for each urban stratum are recommended.